THE USE OF AUTHENTIC MATERIAL IN TEACHING WRITING DESCRIPTIVE TEXT - Gusti Panji Sundana (University of Kuningan, 2017)
This study was conducted to figure out the effectiveness of using authentic materials in teaching writing descriptive text. The study was carried out at one of private universities in Bandung. This study used authentic materials from magazine, newspaper and internet articles as teaching media. The reason of using authentic materials taken from magazine, newspaper and internet was that they could bring the students into a non-threatening atmosphere in the classroom and link the classroom environment with the real world (Clark, 2000). In this study, the qualitative and quantitative methods were applied to gather the data. The data of this study were collected through pretests, posttest, and questionnaires. The findings indicated that using authentic materials in teaching descriptive writing had a significant role in improving students’ writing skill with the significance of 0.05 ( 0.05). The result of t-obs was 3.218 and t-crit was 2.042. This result was supported by the questionnaire results in which the participants showed positive opinions in learning descriptive writing using authentic materials. Finally, it is expected that this study will give beneficial contribution to the teaching of writing for college students in which the technique applied is recommended to be used as an appropriate alternative to improve students’ writing competence.Keywords: descriptive writing, authentic materials